Frequency Support from a Variable-Speed Wind Turbine Generator Using Different Variable Droop Characteristics - Dejian Yang; Jingjiao Li; Xinsong Zhang; Liang Hua (Energies, 2020)
Doubly-fed induction generators (DFIGs) are capable of boosting frequency response capability while preventing the rotor speed from stalling during under-frequency disturbances, by employing variable droop characteristics. However, the frequency response capability during over-frequency disturbances is shortened because the potential for storing the kinetic energy is inversely proportional to the variable droop characteristics used for under-frequency disturbances. This paper designs a frequency control method of a DFIG to boost the frequency response capability during over-frequency disturbances while preserving the frequency response capability during under-frequency disturbances, by employing different variable droop characteristics. The effectiveness of the proposed frequency control method is investigated in a test system. The investigation results under five scenarios with different load variations, wind power penetrations and wind conditions clearly demonstrate that the proposed frequency control method suppresses the maximum system frequency deviations. As such, the proposed frequency control method can provide an effective solution for the frequency control ancillary service of a power system with large integrations of wind energy.